Beyond Trial and Error: A Systematic Development of Liposomes Targeting Primary Macrophages. Issue 3 (3rd February 2021) - Weber, Florian; Ivan, Daniela C.; Proulx, Steven T.; Locatelli, Giuseppe; Aleandri, Simone; Luciani, Paola
Abstract : Monocytes/macrophages are phagocytic innate immune cells playing a pivotal role in tissue homeostasis, inflammation, and antitumor immunity in a microenvironment‐dependent manner. By expressing pattern recognition and scavenger receptors on their surface, macrophages selectively take up pathogens, cellular debris, and often—undesirably—drug delivery systems. On the other hand, the propensity of phagocytic cells to internalize particulate drug carriers is used to load them with a cargo of choice, turning the monocytes/macrophages into a diagnostic or therapeutic Trojan horse. Identifying the ideal physicochemical properties of particulate carriers such as liposomes to achieve the most efficient macrophage‐mediated drug delivery has been object of extensive research in the past, but the studies reported so far rely solely on trial‐and‐error approaches. Herein, a design of experiment (DoE) strategy to identify the optimal liposomal formulation is proposed, fully characterized in terms of size, surface charge, and membrane fluidity, to maximize macrophage targeting. The findings are validated using mouse bone marrow‐derived macrophages, a primary preparation modeling in vivo monocyte‐derived macrophages, thus confirming the robustness and versatility of the systematic and iterative approach and suggesting the promising potential of the DoE approach for the design of cell‐targeting delivery systems. Abstract : Moving away from a typical trial‐and‐error approach, the experimental search space via design of experiment (DoE) strategy, a rational and statistically validated correlation of liposomal physico‐chemical properties to the macrophage targeting are reduced. The findings, validated in mouse bone marrow‐derived macrophages, suggest a translational potential of a DoE for subsequent diagnostic and therapeutic in vivo studies.